Analisis Kondisi Fisik Atlet Pelatda Provinsi Jambi: Korelasi antara Parameter Fisik dan Prestasi Olahraga - Prameswari, Indah Putri; Saputra, Endarman; Murniati, Sri (MAN Insan Cendekia Jambi, 2025)
This research aims to analyze the physical condition of Jambi Province's training center athletes and its relationship with sports achievement. A total of 217 athletes who were members of the Aceh-Sumut 2024 National Sports Week training center were used as research samples. The research method used a correlational quantitative approach with instruments in the form of a series of physical condition tests. The results showed that the physical condition of Jambi Province's training center athletes was generally in the